Synthesis of kaliophilite from high calcium fly ash: Effect of alkali concentration. (December 2022) - Chen, Xianqi; Chen, Jiyuan; Li, Min; Wang, Jinbang; Zhou, Zonghui; Du, Peng; Zhang, Xiuzhi
Abstract: In recent years, the synthesis of zeolite-like products (such as kaliophilite) has been a hot spot due to its high thermal stability, which is excellent inorganic insulating filler and is expected to be widely applied in the field of fireproof materials. Therein, high calcium fly ash is applied to synthesize kaliophilite by hydrothermal method. The microstructure evolution of kaliophilite was investigated, and the effect of alkali concentration on the kaliophilite formation mechanism was analyzed by XRD, SEM, TG-DSC, FT-IR and 29 Si NMR. The results showed that the synthesized kaliophilite presented high thermal stability, and the mass loss was low by 8.83 % at 1000 °C. Hydrothermal promoted the formation of kaliophilite that Q 4 (0Al), Q 4 (1Al), Q 4 (2Al), Q 4 (3Al) and crystal silicon turned into Q 4 (4Al) after hydrothermal transformation. Furthermore, alkali concentration played a key role in the hydrothermal transforming process that low alkali concentration below 8 mol/L had little effect on the synthesis of kaliophilite, while high alkali concentration (≥ 8 mol/L) contributed to the formation of kaliophilite.